Experiential Marketing and Customer Loyalty in Food and Beverage Industry - Sitti Hasbiah; Ilma Wulansari Hasdiansa (International Humanity Advance, Business & Sciences, 2023)
In the highly competitive café and restaurant industry, meeting customer desires is paramount to success. To achieve this, offering unique and value-added experiences alongside technological advancements is essential. This research adopts a quantitative approach, with experiential marketing variables as independent factors and customer loyalty as the dependent variable. Questionnaires were used for data collection, and the study has a cross-sectional time dimension. The sample comprises customers who visited Kampoeng Popsa Makassar at least twice. The study results demonstrate a significant influence of experiential marketing on customer loyalty, as indicated by the high mean values in each experiential marketing dimension. Notably, the "sense" dimension is the most influential factor in driving customer loyalty among the variables. These findings provide Kampoeng Popsa Makassar with valuable insights to enhance customer loyalty and remain competitive. Focusing on enhancing sensory experiences can strengthen their market position, ensuring they continue to meet evolving customer expectations. In a rapidly evolving industry, leveraging experiential marketing strategies is crucial to thrive and differentiate oneself.